The Effect of Managerial Ownership, Financial Leverage, Income Tax, and Company Size on Income Smoothing Practices on Food and Beverage Companies Listed on IDX - Siti Dini; Regina Aguslina Fau (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the effect of managerial ownership, financial leverage, income tax and firm size on income smoothing practices. The type of data used is secondary data. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the period 2016-2020 with a total sample of 13 companies taken by purposive sampling method. The data analysis method used is multiple linear regression analysis. Based on the results of the study, managerial ownership, Financial Leverage, Income Tax, and Company Size simultaneously have a negative and insignificant effect on income smoothing practices in food and beverage companies listed on the IDX in 2018-2020.